Dual inoculation of dark septate endophytes and Trichoderma viride drives plant performance and rhizosphere microbiome adaptations of Astragalus mongholicus to drought. (21st January 2022) - He, Chao; Liu, Chang; Liu, Haifan; Wang, Wenquan; Hou, Junling; Li, Xianen
Summary: Rhizosphere microbiome adapts their structural compositions to water scarcity and have the potential to mitigate drought stress of plants. To unlock this potential, it is crucial to understand community responses to drought in the interplay between soil properties, water management and exogenous microbes interference. Inoculation with dark septate endophytes (DSE) ( Acrocalymma vagum, Paraboeremia putaminum ) and Trichoderma viride on Astragalus mongholicus grown in the non‐sterile soil was exposed to drought. Rhizosphere microbiome were assessed by Illumina MiSeq sequencing of the 16S and ITS2 rRNA genes. Inoculation positively affected plant growth depending on DSE species and water regime. Ascomycota, Proteobacteria, Actinobacteria, Chloroflexi and Firmicutes were the dominant phyla. The effects of dual inoculation on bacterial community were greater than those on fungal community, and combination of P. putaminum and T. viride exerted a stronger impact on the microbiome under drought stress. The observed changes in soil factors caused by inoculation could be explained by the variations in microbiome composition. Rhizosphere microbiome mediated by inoculation exhibited distinct preferences for various growth parameters. These findings suggest that dual inoculation of DSE and T. viride enriched beneficial microbiota, altered soil nutrient status and might contribute to enhance the cultivation of medicinal plants in dryland agriculture.